2006
DOI: 10.1210/en.2005-0640
|View full text |Cite
|
Sign up to set email alerts
|

Testis Structure and Function in a Nongenetic Hyperadipose Rat Model at Prepubertal and Adult Ages

Abstract: There are few data for hormonal levels and testis structure and function during postnatal development in rats neonatally treated with monosodium L-glutamate (MSG). In our study, newborn male pups were ip injected with MSG (4 mg/g body weight) every 2 d up to 10 d of age and investigated at prepubertal and adult ages. Plasma levels of leptin, LH, FSH, prolactin, testosterone (T), corticosterone, and free T4 (FT4) were measured. MSG rats displayed elevated circulating levels of corticosterone and hyperadiposity/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 52 publications
2
31
0
Order By: Relevance
“…e quantitative comparison of the number of Leydig cells among MSG-rats and normal rats remains to be investigated. e present decreased epididymal sperm concentration in rats treated with a high dose MSG (6 g/kg body weight) is consistent with previous studies (9)(10)(11). In addition, our results further demonstrated decreases in the size and weight of the epididymis, some histological changes in the testes, and a depletion of plasma testosterone hormone in rats treated with a high dose of MSG.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…e quantitative comparison of the number of Leydig cells among MSG-rats and normal rats remains to be investigated. e present decreased epididymal sperm concentration in rats treated with a high dose MSG (6 g/kg body weight) is consistent with previous studies (9)(10)(11). In addition, our results further demonstrated decreases in the size and weight of the epididymis, some histological changes in the testes, and a depletion of plasma testosterone hormone in rats treated with a high dose of MSG.…”
Section: Discussionsupporting
confidence: 93%
“…França et al, (9) reported histological alterations of the testes in prepubertal 4 mg/kg body weight of MSG rats and found a significant reduction of spermatogenic cells (SCs) in the testes of adult MSG rats. eir nding of SCs is supported by our present nding that these SCs were sloughing into seminiferous tubule lumen (Fig 2c and 2d).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Production of this hormone takes place in testes (SOLOMON et al 2011). After conversion into dihydrotestosterone, testosterone controls secondary sexual trait development, accessory sex gland development and spermatogenesis (FRANÇA et al 2006). Sperm production and sperm maturation is also regulated by testosterone (RACHMAN & CHRISTIAN 2007;SUN et al 1990) and the number of sperm is an indicator of spermatogenesis effectiveness (RUIZ-PESINI et al 2000).…”
Section: Sexual Maturation In Common Vole Malesmentioning
confidence: 99%